The quality of quality: Toward a semiotics of quality in learning materials - Hansen, Thomas Illum (Learning Tech, 2020)
The conception of good learning materials is an abstraction. Learning materials are always good for something and for someone and less good for other things and for someone else depending on the situated interaction between actors and materials. This article attempts to frame and understand the basic normativity in design, use and research of learning materials as a privileged example of how to understand complex and dynamic processes in teaching. The basic assumption is that research in learning materials has a certain prerogative as the focal point for a study of quality in teaching that the analysis will elaborate as a semiotic of quality. This semiotics of quality will be elaborated and exemplified through an analysis of the problem of representation in teaching, a multidimensional quality theory, a sketch of a meta-language on quality in learning materials, and finally an analysis of the quality of two paradigmatic learning materials.